MANAGERIAL RISK-TAKING AND THE ADOPTION OF ENERGY EFFICIENCY POLICY: IMPLICATIONS ON RESOURCE AVAILABILITY (Journal of International Studies, 2025)
The principal-agent contract motivates managers to take risks to increase shareholders’ returns. A key issue is whether managerial risk-taking decisions are made at the cost of sustainable practices, particularly in relation to environmental protection, which may conflict with profit-seeking activities. This study examines the impact of managerial risk-taking on firms’ energy efficiency practices using a sample of 36 countries from 2006 to 2019. We further investigate how firm size, as a tangible resource, and board size, as an intangible resource, moderate this relationship. Our findings suggest that, although managers take risks to seek higher profitability from investments that may not align with environmental sustainability, intangible resources such as board size can help bridge the gap between profitability and sustainability. However, tangible resources may shift firms’ focus away from sustainable practices, directing attention toward profitable investments that might not be environmentally friendly. In practice, this study highlights the importance of corporate governance, particularly board composition, which plays a key role in contributing to corporate sustainability.